5meCpG Epigenetic Marks Neighboring a Primate-Conserved Core Promoter Short Tandem Repeat Indicate X-Chromosome Inactivation - Brum Machado, Filipe (2014)
X-chromosome inactivation (XCI) is the epigenetic transcriptional silencing of an X-chromosome during the early stages of embryonic development in female eutherian mammals. XCI assures monoallelic expression in each cell and compensation for dosage-sensitive X-linked genes between females (XX) and males (XY). DNA methylation at the carbon-5 position of the cytosine pyrimidine ring in the context of a CpG dinucleotide sequence (5meCpG) in promoter regions is a key epigeneticmarker for transcriptional gene silencing. Using computational analysis, we revealed an extragenic tandem GAAA repeat 230-bp from the landmark CpG island of the human X-linked retinitis pigmentosa 2 RP2 promoter whose 5meCpG status correlates with XCI. We used this RP2 onshore tandem GAAA repeat to develop an allele-specific 5meCpG-based PCR assay that is highly concordant with the human androgen receptor (AR) exonic tandem CAG repeat-based standard HUMARA assay in discriminating active (Xa) from inactive (Xi) X-chromosomes. The RP2 onshore tandem GAAA repeat contains neutral features that are lacking in the AR disease-linked tandem CAG repeat, is highly polymorphic (heterozygosity rates approximately 0.8) and shows minimal variation in the Xa/Xi ratio. The combined informativeness of RP2/AR is approximately 0.97, and this assay excels at determining the 5meCpG status of alleles at the Xp (RP2) and Xq (AR) chromosome arms in a single reaction. These findings are relevant and directly translatable to nonhuman primate models of XCI in which the AR CAG-repeat is monomorphic. We conducted the RP2 onshore tandem GAAA repeat assay in the naturally occurring chimeric New World monkey marmoset (Callitrichidae) and found it to be informative. The RP2 onshore tandem GAAA repeat will facilitate studies on the variable phenotypic expression of dominant and recessive X-linked diseases, epigenetic changes in twins, the physiology of aging hematopoiesis, the pathogenesis of age-related hematopoietic malignancies and the clonality of cancers in human and nonhuman primates.